40Ar/39Ar ages of the sill complex of the Karoo large igneous province: implications for the Pliensbachian-Toarcian climate change. - Jourdan, Fred; Fraud, G.; Bertrand, H.; Watkeys, M.; Renne, P. (American Geophysical Union, 2008)
Reliable geochronological results gathered so far (n = 76) have considerably constrained the timing of the emplacement of the Karoo large igneous province (LIP). Yet strikingly missing from this dating effortis the huge southern sill complex cropping out in the >0.6 x 10(6) km2 Main Karoo sedimentary basin. We present 16 new 40Ar/39Ar analyses carried out on fresh plagioclase and biotite separates from 15 sill samples collected along a N-S trend in the eastern part of the basin. The results show a large range of plateau and miniplateau ages (176.2 +- 1.3 to 183.8 +- 2.4 Ma), with most dates suggesting a -3 Ma (181-184 Ma) duration for the main sill events. The available age database allows correlation of the Karoo LIP emplacement with the Pliensbachian-Toarcian second-order biotic extinction, the global warming, and the Toarcian anoxic event (provided that adequate calibration between the 40K and 238U decay constant ismade). The mass extinction and the isotopic excursions recorded at the base of the Toarcian appear to be synchronous with both the increase of magma emission of the Karoo LIP and the emplacement of the sills.The CO2 and SO2 derived from both volcanic emissions as well as carbon-rich sedimentary layers intrudedby sills might be the main culprits of the Pliensbachian-Toarcian climate perturbations. We propose that the relatively low eruption rate of the Karoo LIP is one of the main reasons explaining why its impact on thebiosphere is relatively low contrary to, e.g., the CAMP (Triassic-Jurassic) and Siberia (Permo-Triassic) LIPs.